2011
DOI: 10.1136/ip.2010.029868
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural characteristics associated with dog bites to children presenting to an urban trauma centre

Abstract: Children are the most frequent victims of dog bites presenting to hospital emergency departments (ED), but there are gaps in understanding of the circumstances of such bites. The objective of this study was to characterise the behavioural circumstances of dog bites by interviewing children ≤17 years (or parent proxies for children ≤6 years) presenting with dog bite injuries to The Children's Hospital of Philadelphia about the bite incident, its setting and associated interactions. Of 203 children enrolled, 51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 15 publications
6
74
0
3
Order By: Relevance
“…We found that injury by dogs, in the majority of cases, occurred where the dog lives, similar to a previous dog bite survey [38,39], whereas most children attacked by cats were in their own home and attacked by their pet cats. Dogs serve as house guards and attack strangers who visit the house, but cats are closer to their owners, and are embraced or even kissed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that injury by dogs, in the majority of cases, occurred where the dog lives, similar to a previous dog bite survey [38,39], whereas most children attacked by cats were in their own home and attacked by their pet cats. Dogs serve as house guards and attack strangers who visit the house, but cats are closer to their owners, and are embraced or even kissed.…”
Section: Discussionsupporting
confidence: 88%
“…Such behavior toward cats is more likely to lead to intentional or unintentional bites or scratches. Similarly, previous studies in developed countries also suggested that wounds were common in arms (hands) by cats, and legs (feet) by dogs [40,41,42], although other studies indicated that dog bites could occur mostly on a child’s face, because a standing dog can be the same height as children [39]. However, in our study, all victims were school-aged children, and were generally taller than a dog or cat.…”
Section: Discussionmentioning
confidence: 75%
“…Reisner et al 7 reviewed the behavioural circumstances associated with bites in children and noted that they could be divided into 2 groups: first, facial bites in younger children by quiet, familiar dogs, which largely occur indoors in the presence of adults, and secondly, bites to the extremities in active school-age or older children by active, unfamiliar dogs outdoors. Information on the context of the injury is important but rarely recorded.…”
Section: Resultsmentioning
confidence: 98%
“…Young children are at a greater risk of zoonotic infection; this is a particular concern for immunocompromised children (reviewed in [82]). In addition, children are at a greater risk of animal bites from a household pet (e.g., about 72%–80% of children are bitten by a familiar dog [83,84,85]). Children under 5 years of age are significantly more likely than older children to provoke animals before being bitten and are most at risk of serious injury [83,84,86,87].…”
Section: Discussionmentioning
confidence: 99%